#### Answer

$\frac{3}{7}$

#### Work Step by Step

$\lim\limits_{x \to -3}\frac{x^2 + 3x}{x^2 - x - 12} = \lim\limits_{x \to -3}\frac{x (x+3)}{(x-4)(x+3)} = \lim\limits_{x \to -3}\frac{x}{(x-4)} = \frac{-3}{-3 - 4} = \frac{3}{7}$

Published by
Cengage

ISBN 10:
1285740629

ISBN 13:
978-1-28574-062-1

$\frac{3}{7}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.